Literature Review : Asuhan Keperawatan Kadar Glukosa pada Lansia Penderita Diabetes Melitus - Mirna Husnanida; Nabila Nabila; Auliya Apriyanti; Muhammad Abizar Al Gifari; Natila Chantika Soedirman; Sri Ariyanti (Nursing Applied Journal, 2025)
Background: Elderly the elderly are individuals aged 60 years and above. Globally the elderly population is growing faster than the younger population. The aging process experienced by the elderly is a process of reducing the body's resistance to internal and external stimuli. in the face of internal and external stimuli. In the aging process the elderly will experience physiological, psychological and social decline, these changes will affect health in the elderly. affect health in the elderly. Diabetes mellitus (DM) or diabetes is a non-communicable disease characterized by high blood sugar levels. by high blood sugar levels. DM occurs when the pancreas does not produce enough insulin to control blood sugar. If people with diabetes mellitus do not carry out treatment, the impact of the occurrence of complications of the disease in people with diabetes mellitus, therefore it is necessary to control or lower blood sugar levels. The purpose of this literature review: To carry out nursing care for the problem of diabetes mellitus in the elderly.Research methods: The search for article data sources was carried out through an inclusion study design using a Literature Review.Results: analysis of journal reviews found differences in the level of effectiveness between foot exercises (50%) and dhikr therapy (5%) and hyperglycemia (45%) where foot exercises were more influential than dhikr therapy in diabetes mellitus.Conclusion: There is an effect of foot exercises on reducing sugar levels in diabetes mellitus.